AxonSeg: Open Source Software for Axon and Myelin Segmentation and Morphometric Analysis - Zaimi, Aldo; Duval, Tanguy; Gasecka, Alicja; Côté, Daniel; Stikov, Nikola; Cohen-Adad, Julien (Frontiers in Neuroinformatics, 2016)
Segmenting axon and myelin from microscopic images is relevant for studying the peripheral and central nervous system and for validating new MRI techniques that aim at quantifying tissue microstructure. While several software packages have been proposed, their interface is sometimes limited and/or they are designed to work with a specific modality (e.g., scanning electron microscopy only). Here we introduce AxonSeg, which allows to perform automatic axon and myelin segmentation on histology images, and to extract relevant morphometric information, such as axon diameter distribution, axon density and the myelin g-ratio. AxonSeg includes a simple and intuitive MATLAB-based graphical user interface and can easily be adapted to a variety of imaging modalities. The main steps of AxonSeg consist of: (i) image pre-processing, (ii) pre-segmentation of axons over a cropped image and discriminant analysis to select the best parameters based on axon shape and intensity information, (iii) automatic axon and myelin segmentation over the full image and (iv) atlas-based statistics to extract morphometric information. Segmentation results from standard optical microscopy (OM), scanning electron microscopy (SEM) and coherent anti-Stokes Raman scattering (CARS) microscopy are presented, along with validation against manual segmentations. Being fully-automatic after a quick manual intervention on a cropped image, we believe AxonSeg will be useful to researchers interested in large throughput histology. AxonSeg is open source and freely available at: https://github.com/neuropoly/axonseg.